Drug Abuse Prevention Strategy in the City of Surabaya - Aisyah, Fatiya Nur; Wibawani, Sri (Borong Newinera Publisher, 2024)
The National Narcotics Agency is a government agency or institution directly appointed by the President to handle drug abuse in Indonesia, including Surabaya City. Drug abuse is a significant social problem in Surabaya City because Surabaya is the second largest business city in Indonesia with a high population density. The National Narcotics Agency (BNN) of Surabaya City has made various efforts to prevent drug abuse. This research aims to find out the drug prevention strategy carried out by the Surabaya City BNN through 3 indicators, namely primary, secondary and tertiary prevention. This research uses qualitative methods with data collection techniques carried out by observation; document study; and in-depth interviews with informants. Determination of informants was done by purposive technique on key informants, then continued with snowball technique. The data validity checking technique used is data triangulation. The results showed that the Surabaya City BNN strategy has been carried out well in primary prevention and secondary prevention, but in tertiary prevention the Surabaya City BNN still does not have sufficient facilities and infrastructure to carry out inpatient rehabilitation.